Chorionic sculpture of eggs in the subfamily Dismorphiinae (Lepidoptera: Papilionoidea: Pieridae) - Llorente-Bousquets, Jorge; Nieves-Uribe, Sandra; Flores-Gallardo, Adrián; Hernández-Mejía, Blanca Claudia; Castro-Gerardino, Jimena (Zootaxa, 2018)
This is the second exploration, comparison, and analysis of the chorion of species (45 sspp.) of the subfamily Dismorphiinae (Pieridae). This study includes nearly 50% of the species of the subfamily, including six of the seven genera in its two subtribes: Leptidea (Leptideini), Enantia, Pseudopieris, Lieinix, Moschoneura, and Dismorphia (Dismorphiini). The material studied originates from more than three dozen localities in six different countries on three continents (America, Asia, and Europe) and two biogeographical regions, the Palearctic and Neotropical, over the last 20 years. We have corrected and added information regarding several morphological aspects of the chorion. The precision of the citriform configuration and the elimination of the meloniform shape in the egg of Dismorphiini were determined with detailed observations on the maturation of the chorion in the ovarioles where each stage appears in a linear sequence. We discerned that the meloniform states correspond to incompletely differentiated or immature eggs. This was confirmed by the study of new samples of Dismorphia amphione, D. eunoe, and D. lewyi. The chorion of Dismorphiinae is basically plesiomorphic with respect to those of Coliadinae and Pierinae because it lacks several typical synapomorphies of these subfamilies, such as the presence of micro-grid and/or perimicropylar and apex differentiation, respectively. The eggs of each Dismorphiinae genus can be diagnosed by a combination of chorionic features, although sometimes by one or more plesiomorphies or apomorphies in each genus, with respect to the form or character states in axes, ribs, and poles in the grid of the three regions of the egg - two polar regions and one equatorial (basal, medial, and apical). Leptidea and Enantia show the most generalized grid pattern; however, two genera retain several plesiomorphies with respect to the undifferentiated axes or a small number of short axes (Pseudopieris), as well as many equidistant ribs (Lieinix). The chorionic grid of Moschoneura, although practically lacking short axes, shows the fewest number of axes in the entire subfamily (eight aligns it with Pseudopieris). The chorionic grid in Dismorphia is highly diverse, as it shows the most derived states; however, it comprises symplesiomorphies or atavisms in two groups of species, which aligns them closer to Lieinix or Pseudopieris, but we do not take them into account in some cases where they are convergences or structural parallelisms. It seems that the combination of the shape and its length:width ratio is correlated with the alar configuration (design, sexual dimorphism, and coloring patterns) and separates three groups of species in Dismorphia, and often correlates with the number of ribs. This also coincides with the Batesian participation in the number of mimetic complexes in which a subgroup of species and their stenoecy are integrated within the primary forests. Finally, two schemes are presented that synthesize and illustrate the changes or progression of the form and chorionic grid in the genera of the subfamily.